The Role of The Trade Agency in Overseeing Unfair Competition in Wonogiri District, A Case Study of Wonogiri District Market - Ardha Tri Adi Prasetyo; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2024)
The purpose of this research is to identify the Role of the Trade Office in Supervising Unfair Competition in Wonogiri Regency Case Study of Wonogiri Regency Market. The empirical juridical research approach is determined in this study using qualitative research methods because the researcher intends to understand the phenomenon of what is experienced by the research subject such as behavior, legal efforts, and actions that have been taken, directly by means of descriptions in the form of words and language, in a special context. The purpose of using qualitative methods is to seek a deep understanding of a subject matter, facts, or reality in it. Researchers use descriptive qualitative research because the authors want to describe the results of the research not with numbers but using written words and describing the results. It can be concluded that the Wonogiri City Trade Office has carried out price controls to overcome the problem of unfair competition that has been going on for a long time in the Wonogiri Regency market. Various efforts such as market operations and socialization have been carried out to overcome monopolistic practices and unfair trade competition in the Wonogiri Regency area.